2022
DOI: 10.2147/ppa.s378081
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Motivating Factors Regarding COVID-19 Vaccination in Latinx Older Adults in Chicago: A Local, Qualitative Perspective

Abstract: Historically marginalized communities disproportionately impacted by the pandemic are demonstrating lower uptake of COVID-19 vaccines. To facilitate the development of culturally tailored, language concordant educational materials promoting COVID-19 vaccination, we first explored older Latinx adults' awareness, attitudes, and beliefs about COVID-19 vaccines and factors involved in vaccination decisions within their communities. Patients and Methods: Individual, semi-structured interviews were conducted with 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Additionally, we found that some of the vaccinated participants had previously been quarantined due to COVID-19 exposure or had a pre-existing chronic condition. This suggests that individuals who are at higher risk for severe illness from COVID-19, especially those with co-morbidities, may be more likely to prioritise vaccination to protect their health, again similar to other studies [ 120 , 122 125 ]. Consequently, future public health campaigns need to consider these additional risk factors as well and target outreach and education efforts towards individuals who may be more vulnerable to severe COVID-19 illness.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, we found that some of the vaccinated participants had previously been quarantined due to COVID-19 exposure or had a pre-existing chronic condition. This suggests that individuals who are at higher risk for severe illness from COVID-19, especially those with co-morbidities, may be more likely to prioritise vaccination to protect their health, again similar to other studies [ 120 , 122 125 ]. Consequently, future public health campaigns need to consider these additional risk factors as well and target outreach and education efforts towards individuals who may be more vulnerable to severe COVID-19 illness.…”
Section: Discussionsupporting
confidence: 83%
“…Other investigations related to COVID-19 vaccination were carried out from manifold angles, covering various social groups [ [49] , [50] , [51] , [52] ] or territories [ [53] , [54] , [55] , [56] , [57] ]. Therefore, in Africa, a continent with a large population, beyond a cumbersome management of vaccination campaigns, supplementary incentives are needed to consider all social categories, those related to age or place of origin [ 58 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This inadequacy of the health information environment has led to further marginalisation of culturally and linguistically diverse communities. Poor outcomes including lower knowledge and understanding about COVID-19, negative attitudes and behaviours related to COVID-19, have been observed among different cultural and linguistic groups in many countries, including Australia [37,39,[70][71][72][73]. In the authors' Australian national survey, people who spoke another language at home reported: a greater perceived difficulty in finding health information; a lower perceived risk of COVID-19; a lower understanding of COVID-19 prevention behaviours; a higher endorsement of misinformation; and a lower willingness to be vaccinated compared to people who spoke English [40].…”
Section: Covid-19 Understanding Attitudes Misinformation Beliefs and ...mentioning
confidence: 99%
“…Some communities also exhibit a compromised trust in government advice, based on a history of racism in medical research and care, uncertainty about visa status, and a lack of government support for those in precarious or hazardous employment. For instance, whilst Light et al reported that some Latino Americans trusted COVID-19 vaccines, others worried the vaccines had been manipulated [73]. Fear about attending a vaccine site also was reported due to immigration status as well as concerns about missing work due to short-term vaccination side effects.…”
Section: Covid-19 Understanding Attitudes Misinformation Beliefs and ...mentioning
confidence: 99%